Food intake and eating patterns of underprivileged women in a metropolitan city - Patil, Rita S.; Kaku, Nidhi (International Journal Of Community Medicine And Public Health, 2021)
Background: India faces the burden of dual-malnutrition due to several influences affecting the dietary-pattern. These causes include economic and social factors. Many migrants come to metropolitan cities in search of livelihood. This study aimed to study the dietary intake of 100 low-socioeconomic women in Mumbai. Methods: These participants were migrants from various states. They lived in slums and worked to supplement family income. A detailed food-frequency questionnaire and a 24-hour dietary-recall were obtained from them. Results: All participants consumed white rice, junk-food and oil. Ninety-five subjects consumed potato, milk and sugar. Areca nut was regularly consumed 33 women. According to the Indian recommended dietary allowances (RDA, 2020), none of the subjects met their energy and protein needs. However, their average fat intake exceeded the recommendation. Older women (33-40 years) had significantly higher intake of calories and fat, compared to younger women (25-32 years) (p=0.03). Fat intake was positively correlated to the abdominal obesity (p=0.04). These women had a low fruit, vegetable, protein and overall caloric intake but a high fat, junk-foods, areca nut and sugar intake. Conclusions: Poor economic conditions and affordability may cause inappropriate dietary-patterns resulting in dual malnutrition which can put these women at a high-risk for metabolic diseases.